Synthesis of BiOCl/C/g-C3N4 Z-scheme heterojunction: mercury lamp-driven heterojunction for efficient degradation of phenol - Song, Kai; Chen, Wan-ping; Wang, Run-quan; Zhang, Yue-rong; Tian, Yuan; Li, Jia-xian; Wang, Guo-ying; Shi, Gao-feng (Research on chemical intermediates, 2023)
Designing photocatalysts to remove organic pollutants are of great significance in the environmental field. Herein, BiOCl/C/g-C 3 N 4 photocatalyst was synthesized with biochar, BiOCl, and g-C 3 N 4 . Biochar was first used as an electronic medium to accelerate charge carrier separation. Moreover, the formation of the built-in electric field between BiOCl and g-C 3 N 4 interface inhibits the electron–hole recombination during the photocatalytic process. The characterization results show that the Z-scheme heterojunction structure was successfully prepared. The BiOCl (0.5) C (0.03) g-C 3 N 4(0.97) photocatalyst had up to 96.9% degradation of phenol under mercury lamp irradiation. The rate constant of the photodegradation reaction process is 0.38706 h −1 , which is 2.1 times that of pure BiOCl. And photocatalyst has satisfactory stability, which a three-cycle retention rate was 97.6%. In addition, the reaction mechanism was studied, and the photogenerated carrier transferring pathways of BiOCl/C/g-C 3 N 4 Z-scheme photocatalysts were proposed. The photocatalyst offers new ideas for the Z-scheme heterojunction photocatalyst. Graphical Abstract